ROLE OF CONSUMER BEHAVIOUR ON THE ADOPTION OF ONLINE SHOPPING IN NAIROBI CITY COUNTY - A CASE OF NAIVAS SUPERMARKET - Ngumba, Anne Wanjiku; Kagiri, Dr. Assumpta (European Journal of Business and Strategic Management, 2018)
Purpose: The main aim of the research was to find out the role of consumer behaviour on the adoption of online shopping in Nairobi County. Methodology: The study employed a descriptive research design. A sample of 285 participants was used to collect the data. Data for this study was collected mainly from primary source through questionnaires with both open and closed questions. Data was analysed using descriptive statistical techniques and inferential statistics. The data was presented through frequency distribution tables and charts to address the objective of the study. Results: The findings obtained show that perceived benefits from online shopping was an important factor to consumer behaviour and acceptance of online shopping. Both online shopper and non-online shopper agree there is more derived benefits from online shopping. Online shopping users were noted to be sceptical on the risks associated with online transaction while the non-online users strongly agreed that the amount of risk in online shopping were very high. There was also a strong affirmation that psychological factors are important to restore confidence in online shopping including security of the information, level of trust and control over the transaction. Finally online shopping was influenced by the design of the website. Policy recommendation: The study recommends studies targeting other supermarkets. This is vital since the information garnered can help marketing managers learn how to best deal with new technologies and how consumers react to these new technologies.